STATUS MUTU AIR DAN BEBAN PENCEMARAN SUNGAI SAIL BAGIAN HILIR, KOTA PEKANBARU, PROVINSI RIAU PADA KONDISI PASANG SURUT - Yuliati Yuliati; Efawani Efawani; Muhammad Fauzi; Galeh Suryo (EnviroScienteae, 2022)
The Sail River is the position in the center of Pekanbaru City and is affected because of the tides. Urban pollution is a significant giver to the Sail River of water quality degradation. The study was conducted between June and August to assess estimation pollution load Sail River and pollution levels using the Pollution Index method. Water quality parameters measured are physical (temperature, TSS) and chemical (pH, dissolved oxygen, BOD, COD, Pb, oil and grease, nitrate, as well as phosphate). The results showed that the Sail River was classified as lightly polluted at high tide and low tide. The pollution index value at high tide is higher with a range of 3.65-3.92 than at low tide (2.93-3.39). TSS is the highest pollution load of the Sail River that a value of 1079.83 mg/second at high tide and 1075.29 mg/second at low tide. The lowest pollution load is oil and grease at low tide (0.47 mg/second). Thus, it is necessary to control the level of water pollution in the Sail River.